Construction industry: fragmented or integrated? (Gaceta Técnica, 2022)
Lately terms are found within the AEC (Architecture, Engineering and Construction) industry, such as collaborative planning, concurrent design, integrated teams, planning and early integration. These respond to non-traditional methodologies that bring high benefits of time savings, costs, progress in productivity and quality, notable improvements in construction, as well as in the fluidity of information and communication of the project.
Keywords: industry AEC; DBB-Design-Bid-Build; Building Information Modeling